2021
DOI: 10.1002/pan3.10197
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder priorities determine the impact of an alien tree invasion on ecosystem multifunctionality

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 68 publications
0
23
1
Order By: Relevance
“…The stakeholder groups prioritised the same ES in each region, thus indicating common, possibly universal, patterns of prioritisation across Germany, at least within high biodiversity cultural landscapes such as these. The patterns of priority observed here differ from those in most previous studies (Linders et al, 2021;Martin-Lopez et al, 2012;Quintas-Soriano et al, 2018;Washbourne et al, 2020) in that stakeholders are less specialised and less polarised (e.g. each group exclusively prioritising just a few favoured ES).…”
Section: Discussioncontrasting
confidence: 95%
“…The stakeholder groups prioritised the same ES in each region, thus indicating common, possibly universal, patterns of prioritisation across Germany, at least within high biodiversity cultural landscapes such as these. The patterns of priority observed here differ from those in most previous studies (Linders et al, 2021;Martin-Lopez et al, 2012;Quintas-Soriano et al, 2018;Washbourne et al, 2020) in that stakeholders are less specialised and less polarised (e.g. each group exclusively prioritising just a few favoured ES).…”
Section: Discussioncontrasting
confidence: 95%
“…In the French Alps, for example, surveys identified that aesthetic value of mountain grasslands was essential to local farmers and tourists, and related not only to flower diversity, but also to the absence of a build-up of plant litter 82 . As another example, the cover of woody species can be used as an indicator of the vital regulating service of shade provision in East African grasslands 83 . Visually estimable indicators can also be employed in such assessments to ensure both relevance and cost-effectiveness.…”
Section: Standardised Assessmentmentioning
confidence: 99%
“…The creation of such indices can be achieved by adapting approaches developed for measuring the co-delivery of multiple ecosystem services based on stakeholder preferences 74,84 , and other participatory multi-criteria analyses of ecosystem services 85 . Both approaches can also be used to weigh the measures included in the calculation of the index, for example by encouraging representatives of different stakeholder groups to assign scores to the ecosystem services considered 83 . In the final step, we suggest that conclusions from this standardised approach are used to inform management decisions regarding which restoration options should be employed and where.…”
Section: Standardised Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, at very low intensity fodder production might not be profitable enough for farmers, resulting in no benefit despite some supply, and with a risk of pasture abandonment. While tailored supply-benefit relationships have been rarely used in multifunctionality metrics due to the difficulty in defining their shape, their integration could greatly improve model predictions (Manning et al 2018, Linders et al 2021). Both the prioritisation of services by stakeholders, and supply-benefit relationships, are also likely to change in time and space (Boesing et al 2020), e.g.…”
Section: Discussionmentioning
confidence: 99%